CXCR7 Targeting and Its Major Disease Relevance - Wang, Chuan; Chen, Weilin; Shen, Jianzhong (Frontiers in Pharmacology, 2018)
Chemokine receptors are the target of small peptide chemokines. They play various important roles in physiological and pathological processes. CXCR7, later renamed ACKR3, is a non-classical seven transmembrane-spanning receptor whose function as a signaling or non-signaling scavenger/decoy receptor is currently under debate. Even for cell signaling mechanism, there has been inconsistency on whether CXCR7 couples to G-proteins or β-arrestins. Several reasons may contribute to this uncertainty or controversy. In one hand, it has been neglected that CXCR7 has more than five natural ligands and unfortunately, most of the prior research only studied SDF-1 (CXCL12) and/or I-TAC (CXCL11); on the other hand, there are mounting evidence supporting ligand and tissue bias for receptor signaling, but limited such information is available for CXCR7. In this review we focus on summarizing the endogenous and exogenous ligands of CXCR7, the main diseases related to CXCR7 and the biased signaling events happening on CXCR7. These three aspects of CXCR7 pharmacologic properties may explain why the contradicting opinions of whether CXCR7 is a signaling or non-signaling receptor exist. Further, potential new direction and perspective for the study of CXCR7 biology and pharmacology are highlighted.